Achilles tendon morphology adaptations in chronic post-stroke hemiparesis: a comparative analysis with neurologically intact controls - Liang, Jing Nong; Bashford, Greg; Kulig, Kornelia; Ho, Kai-Yu (Frontiers in Sports and Active Living, 2025)
Introduction In individuals with chronic post-stroke hemiparesis, slow walking speed is a significant concern related to inadequate propulsion of the paretic limb. However, an overlooked factor is this population's altered morphology of the Achilles tendon, which may compromise the propulsive forces by the paretic limb. This study aimed to explore changes in Achilles tendon morphology, including gross thickness and intra-tendinous collagen fiber bundle organization, following stroke-induced brain lesions. Methods Fifteen individuals with chronic post-stroke hemiparesis (at least 6 months post-stroke) and 19 neurologically intact controls participated. Ultrasound imaging was used to evaluate Achilles tendon thickness and collagen organization in the paretic and non-paretic limbs of post-stroke participants, as well as in the right limb (control limb) of the neurologically intact control group. Results and discussion Compared to control individuals, the paretic limb in individuals post-stroke showed increased tendon thickness at the Achilles tendon insertion and 2 cm above it. The collagen fiber bundle at the Achilles tendon insertion of the paretic limb showed reduced organization compared to that in the control limb. Individuals post-stroke also exhibited slower walking speed, and increased plantarflexor muscle tone in the paretic limb compared to controls. In conclusion, individuals with chronic post-stroke hemiparesis demonstrated tendon thickening and collagen disorganization in the paretic limb, particularly at the insertion site of the Achilles tendon, likely due to an abnormal loading environment influenced by increased plantarflexor muscle tone, muscle co-activation, and muscle disuse and atrophy. These changes may increase tendon compliance, impair force transmission and propulsion, and contribute to slower walking speed. Addressing Achilles tendon integrity should be incorporated as a component of strategies to improve neuromuscular control in this population.